Comparison of the distributions of bremsstrahlung X-rays, Cerenkov light, and annihilation radiations for positron emitters. (October 2021) - Nakanishi, Kouhei; Yamamoto, Seiichi
Abstract: Positron emission tomography (PET) is a powerful tool because we can acquire functional information of tissue from the images with high sensitivity and relatively high spatial resolution. However, high-spatial-resolution PET imaging for high-energy positron emitters is difficult because the positrons have a long range and annihilation radiations are emitted at the endpoints of the positrons' trajectories. Along the trajectories, Cerenkov light (CL) is also emitted in advance of the emission of annihilation radiations. Hence, CL can be used for the imaging of high-energy positron emitters. Bremsstrahlung X-rays are also emitted along the trajectories of positrons, and imaging is possible. However, the differences in the spatial distributions of these three types of radiations are not obvious. Because CL and bremsstrahlung X-rays are produced before the endpoint of the positron, high-spatial-resolution imaging may be possible for high-energy positrons. In this study, to clarify this point, we simulated the spatial distribution of CL, bremsstrahlung X-rays, and annihilation radiations using Monte Carlo simulation and compared the distributions. The distributions of the bremsstrahlung X-rays and CL were smaller than those of the annihilation radiations in case of high energy positrons, and we found that the distributions of bremsstrahlung X-rays nearly matched those of CL for high-energy positron emitters. We concluded that CL and bremsstrahlung X-ray imaging have higher spatial resolution than annihilation radiation imaging for MeV ordered positron emitters, and thus they are promising for high-spatial-resolution imaging of high-energy positron emitters such as O-15 for ion therapy and Ga-68 for PET imaging. Highlights: Bremsstrahlung X-ray (BX) from PET tracer is promising for in-vivo imaging of rat. Distributions of BX were shaper than those of 511-keV photon emitted by positron. Distributions of BX matched those of Cerenkov light (CL) for high-energy positron. CL and BX imaging have high spatial resolution for MeV ordered positron emitters.